TEAMS GAMES TOURNAMENT SEBAGAI UPAYA PENINGKATAN KEMAMPUAN BELAJAR MAHASISWA PADA MATA KULIAH MATEMATIKA EKONOMI - FACHRURROZIE, -; Anisyukurillah, Indah (Dinamika Pendidikan, 2009)
The objective of this study is to measure and obtain the empirical proof that concerned to the effectiveness and significance in applying Teams Games Tournament learning model that was presented in teaching learning process in Economics Mathematics subject in improving the students’ learning ability. This study used 3 cycles and involved 67 students from the 1st semester of regular class, Accounting Education Program, S1 Degree on Accounting Department, Economics Faculty, Semarang State University. Result of this study was to apply Economics Mathematics through Teams Games Tournament model learning in Quadrat Function Topic with the sub topics were Demand Function, Supply Function, Market Equilibrium, Tax and Subsidy Influences to improve the students’ ability and skill in teaching learning process. It was seen that score average from 11 teams from Cycle I, II and III was getting increased about 60,11%; 87% and 96,88%. Therefore, that result has obtained the target because the students who got the score higher than 70 were more than 80 %, thus this teaching method can be said successfull. Key Words : Teams Games Tournament,Economics Mathematics